2019
DOI: 10.1155/2019/4942578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Geomembrane Effect Based on Mobilized Shear Stress due to Localized Sinking

Abstract: Installing geosynthetic reinforcement at the bottom of the embankment will provide positive support for subgrade stability and settlement control, if there is a void or a weak foundation. In routine design work, the geomembrane effect must be well estimated and the tensile strain should be precisely predicted. Conventional analytical methods often adopt the limit state method to calculate the overlying load on the deflected geosynthetic. However, this assumption does not necessarily apply to all conditions, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Huang [10] revealed that the friction angle and particle size within the soil had obvious influence on the deformation and tension of the reinforcement material with the help of a trapdoor test model. Lu [11] analyzed the stress-strain characteristics of the reinforced body and found that the peak tensile strain in the bottom layer of the geogrid was at the edge of the void. Huckert [12] analyzed the effect of void span on soil displacement and reinforced body deformation during traffic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Huang [10] revealed that the friction angle and particle size within the soil had obvious influence on the deformation and tension of the reinforcement material with the help of a trapdoor test model. Lu [11] analyzed the stress-strain characteristics of the reinforced body and found that the peak tensile strain in the bottom layer of the geogrid was at the edge of the void. Huckert [12] analyzed the effect of void span on soil displacement and reinforced body deformation during traffic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Lime-FA-CS (or gravel) is a widely used road base material in China [11,12], and it has many advantages such as steady strength development, simple construction, and the utilization of waste FA, but unfortunately the shrinkage cracks often occur, and the early strength of it is very slow. ese disadvantages baffle it from being utilized widely [11,13,14]. It should be known that the mix ratio of binder and CS (or gravel) is also another factor affecting the mixture's strength and anticrack properties.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of some high-tech equipment, the strength mechanism of the microstructure of lightweight mixture can be explained and quantified more easily [15,16]. Moreover, the mechanical constitutive model of the lightweight mixture can also be established, and the prediction of strength and deformation of these lightweight fillers have a good guiding role in engineering application [17][18][19]. However, these current research studies are mainly based on ideal conditions.…”
Section: Introductionmentioning
confidence: 99%